2020
DOI: 10.5114/ait.2020.96560
|View full text |Cite
|
Sign up to set email alerts
|

Consensus of the Study Group for Point-of-Care Lung Ultrasound in the intensive care management of COVID-19 patients

Abstract: According to currently available data, from 5% to 16% of patients tested positively for COVID-19 required admission to an intensive care unit (ICU) due to respiratory failure and the necessity to introduce mechanical ventilation [1,2]. Respiratory failure is the dominating medical issue in the course of this disease. It is widely acknowledged that computed tomography is the gold standard for diagnosing lung diseases, and it facilitates the visualisation of interstitial inflammatory lesions that are found also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In our study, we based our score on the progressive loss of aeration described in pneumonia [ 20 , 39 , 48 ]. However, we discriminated between subpleural and lobar consolidations as the most relevant finding [ 10 , 38 , 43 ] due to their contribution to uneven alveolar ventilation–perfusion [ 8 , 25 , 27 ]. Our data showed that LUS scores obtained at D1 predicted the P/F ratio when using comprehensive cohort data.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we based our score on the progressive loss of aeration described in pneumonia [ 20 , 39 , 48 ]. However, we discriminated between subpleural and lobar consolidations as the most relevant finding [ 10 , 38 , 43 ] due to their contribution to uneven alveolar ventilation–perfusion [ 8 , 25 , 27 ]. Our data showed that LUS scores obtained at D1 predicted the P/F ratio when using comprehensive cohort data.…”
Section: Discussionmentioning
confidence: 99%
“…B-line artifacts are significant in diagnosing many diseases that affect the pulmonary interstitial space and alveoli [1,6]. These artifacts are defined as laser-like vertical re-verberation artifacts arising from the pleural line, extending to the bottom of the screen (irrespective of the set depth), moving along with the lung slide, and leading to the disappearance of A-lines [7].…”
Section: Introductionmentioning
confidence: 99%
“…This form of education may be successfully applied in the teaching and learning of lung ultrasound techniques. 54 Moreover, Pivetta et al reported that a patient self-performed lung ultrasound in the home with a hand-held device under the guidance of a physician using a novel teleguidance platform is also possible. Maximum isolation, thus, can be obtained.…”
Section: Of Lus In Covid-19 Pneumoniamentioning
confidence: 99%